Relevance of Ambedkar’s Political Philosophy in Contemporary India - VAISHALI MUNDEL (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Dr. B.R. Ambedkar’s political philosophy, rooted in the principles of liberty, equality, and fraternity, continues to resonate with pressing issues in contemporary India. As the chief architect of the Indian Constitution, Ambedkar envisioned democracy not merely as a form of government but as a tool for social transformation. This article critically examines the core tenets of Ambedkar’s political thought—social democracy, constitutionalism, annihilation of caste, and economic justice—and evaluates their relevance against today’s backdrop of caste-based violence, economic disparity, and political polarization. Drawing on his contributions to labor rights, his radical opposition to the caste system, and his strategic embrace of Buddhism as a form of resistance, the paper explores how Ambedkar’s ideas have been both co-opted and misinterpreted by contemporary political forces. It further analyzes the dilution of Ambedkarite politics among Dalit elites and NGOs, the ideological tensions and potential alliances with Left movements, and the growing urgency of embedding Ambedkar’s vision in current governance and civil society. Ultimately, the article argues for a renewed commitment to Ambedkar’s emancipatory framework as a means to safeguard India’s democratic ethos in the face of rising authoritarianism and social inequality.